Natural killer cell activity influences outcome after T cell depleted stem cell transplantation from matched unrelated and haploidentical donors - Lang, Peter; Pfeiffer, Matthias; Teltschik, Heiko-Manuel; Schlegel, Patrick; Feuchtinger, Tobias; Ebinger, Martin; Klingebiel, Thomas; Bader, Peter; Schlegel, Paul-Gerhardt; Beck, James; Greil, Johann; Handgretinger, Rupert (Best practice & research, 2011)
Lytic activity and recovery of natural killer (NK) cells was monitored in pediatric patients with leukemias (ALL, AML, CML, JMML) and myelodysplastic syndromes after transplantation of T cell depleted stem cells from matched unrelated (n = 18) and mismatched related (haploidentical, n = 29) donors. CD34 + selection with magnetic microbeads resulted in 8 × 103/kg residual T cells. No post-transplant immune suppression was given. NK cells recovered rapidly after transplantation (300 CD56+/μL at day 30, median), whereas T cell recovery was delayed (median: 12 CD3+/μL at day 90). NK activity was measured as specific lysis of K 562 targets several times (mean: 3 assays per patient). Four temporal patterns of lytic activity could be differentiated: consistently low, consistently high, decreasing and increasing activity. Patients with consistently high or increasing activity had significantly lower relapse probability than patients with consistently low or decreasing levels (0.18 vs 0.73 at 2 years, p < 0.05). The subgroup of patients with ALL showed similar results (0.75 vs 0.14 at 2 years, p < 0.05). Speed of T cell recovery had no influence. These data suggest that both achieving and maintaining a high level of NK activity may contribute to prevent relapse. Since NK activity could be markedly increased by in vitro stimulation with Interleukin 2 (IL-2), in vivo administration should be considered.
Gesehen am 12.07.2022